A concept of shear wall for the design of high-rise buildings construction - Abu Eusuf, Muhammad (IIUM Press, 2011)
This chapter is described the analysis and design process of shear wall, which is applied to high- rise building construction. Shear wall resists lateral earthquake force and wind force. Besides, Buildings with cast-in-situ reinforced concrete shear walls are widely used in earthquake-prone area and regions in the world. Research method has been confined in library research and employed software for analysis. The analytical accuracy of complex Shear Wall Systems has always been of concern to the Civil and structural Engineering system. The software of this system is performed on the platform of modeling and the models of this system are usually idealized as line elements instead of continuum elements. Single walls are modeled as cantilevers and walls with openings are modeled as pier/ spandrel systems. In order to find the stiffness, the simple systems models can provide reasonable results. It has always been accepted that a scale based model in the FEM is exact and justifiable.